(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of the research were to (1) study the community leadership components of local fishing villages in the Central Region, (2) create the model of community leadership development of local fishing villages in the Central Region, and (3) assess the model of community leadership development of local fishing villages in the Central Region by applying the Mix Methods Research with in-depth interviews of 15 local experts and Sampling Survey from 400 residents of local fishing villages. The research analyzed and synthesized the data with statistical data analysis methods i.e. Exploratory Factor Analysis—EFA, and used Descriptive Statistics such as Mean— x̅, Standard Deviation—SD, to assess the adequacy and practicability of the model. The results of the research were as follows: • 1. There are 6 areas of the community leadership components of local fishing villages in the Central Region including (1) behavior and management of community leader for building workplace relationship, (2) confidence and trust building, (3) creativity and ability to solve the community’s problems, (4) fair, transparent, and honest management of the human resource, work, and community, (5) creation of community leader’s credible image, and (6) the governance that corresponds with community’s goals. • 2. The model of community leadership development of local fishing villages in the Central Region, conclusion, is that the leaders must develop the leadership in these areas including (1) development on behavior and management of community leader for building workplace relationship, (2) development on confidence and trust building, (3) development on creativity and ability to solve the community’s problems, (4) development on fair, transparent, and honest management of the human resource, work, and community, (5) development on the creation of community leader’s credible image, and (6) development on governance that corresponds with community’s goals. • 3. The assessment of the model of community leadership development of local fishing villages in the Central Region found that the overall model is adequate and practical for developing the community leadership of local fishing villages in the Central Region the most.